ARID5B rs10821936 and rs10994982 gene polymorphisms and acute lymphoblastic leukemia: relation to disease susceptibility and outcome. (18th August 2019) - Mosaad, Youssef M.; Khashaba, Mohamed; Darwish, Ahmad; Darwish, Mohamed; Elwassefy, Mona; Abdelmabood, Souzy; Fawzy, Iman M.; Youssef, Laila F.; Elbasiouny, Rehab A.
Abstract: ARID5B rs10821936 and rs10994982 single nucleotide polymorphism (SNP) have been associated with the risk of acute lymphoblastic leukemia (ALL) in different ethnic populations. We investigated the association between the ARID5B rs10821936 C > T, rs10994982 A > G, and susceptibility to ALL in a cohort of Egyptian individuals and investigated their role in relation to disease outcome. Real-time PCR typing was done for ARID5B rs10821936 and rs10994982 SNPs for 128 pediatric ALL (pALL), 45 adult ALL (aALL), and 436 healthy controls. Significant risk associations were found between the C allele ( p < 0.001, OR = 2.02), CC genotype ( p < 0.001, OR = 2.72), CT genotype ( p = 0.011, OR = 1.45) of ARID5B rs10821936 and pediatric ALL especially T-ALL and adult ALL ( p < 0.05). The CA haplotype (C allele of rs10821936 + A allele of rs10994982) was associated with the risk of ALL either pediatric ALL or adult ALL ( p < 0.001). In the studied Egyptian population, it can be concluded that the C allele, CC, and CT genotypes of ARID5B rs10821936 and the CA haplotype may be a susceptibility risk factor for pediatric and adult ALL. However, the SNPs of ARID5B rs10821936 and rs10994982 were not found to be strongly associated with ALL outcomes.